An analysis of East Asian currency area: Bayesian dynamic factor model approach - Toan, N.N. (Informa UK Limited, 2010)
There has recently been an increasing interest in the establishment of a common currency area in East Asia in the aftermath of the East Asian financial crisis. In this article I examine the desirability and feasibility of forming a currency area in the region by checking the symmetry of shocks as an important criterion of the theory of Optimum Currency Area. I employ a dynamic factor model to decompose aggregate output into world, regional and country-specific components and estimate the model using a Gibbs sampling simulation. Persistent properties of those components are examined and variance decomposition analysis is performed to investigate the role of each component in output variance. The European Monetary Union, with the successful launch of the euro, is the natural benchmark for comparison. Based on variance analysis, it is found that East Asian countries, on average, are less plausible candidates for a currency area than European counterparts. However, a subgroup of countries in East Asia is as qualified as those in Europe. Given the ongoing integration in East Asia, it is not premature to prepare for such a currency area in this region.